KLINIK UTAMA REHABILITASI MEDIK DI BANJARMASIN - Sukma, Dhia Ulfairuz; Oktaviana, Anna (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2020)
Along with the development of medical science and society needs Kementerian Kesehatan (Kemenkes) released a program in 2017, called JKN or Jaminan Kesehatan Nasional about improvement and build of quality of health infrastructure. Based on that program Kementrian Kesehatan expects the distribution of health facilities in each region. In Banjarmasin, rehabilitative health facilities is still not enough qualitatively and quantitatively, one of the rehabilitation health facilities is a medical rehabilitation facility. Medical rehabilitation’s patients in Banjarmasin hospitals always increase, so that hospital services become less than optimal, therefore additional outpatient services are needed through the clinic In reality amount of medical rehabilitation clinics are still not spread in Banjarmasin and the quality of clinics in Banjarmasin has not fulfilled the requirements of the physical environment where the physical environment is the biggest factor that affects the healing process. The healing environment approach is used as a method and concept of problem-solving. The method used is to determine and analyze the facts from the medical rehabilitation service, then applying the healing environment aspect to space, both internal and external space. The healing environment aspect consists of nature, senses, and psychology.